In Situ Assessment of HVAC System Impact in Façades of a UNESCO World Heritage Religious Building - Kelsey Williamson; Antonio Martinez-Molina; William Dupont (Anuari d’Arquitectura i Societat)
The maintenance of historic buildings’ optimal indoor environments for structural integrity and collections’ preservation, are inherently complex, multifaceted goals. Moreover, indoor environments do not only affect collections and building"”the occupants’ satisfaction must also be considered. This research evaluates the impact of thermal and humidity problems caused by a HVAC condensing unit on a 265-year-old wall in a UNESCO World Heritage Site in the hot and humid climate of San Antonio, Texas (USA). A field investigation of Indoor Environmental Quality (IEQ) particularly focused on the HVAC impact on a wall nearby was carried out. The case study is a unique historic settlement that includes a limestone church which reflects a similar typology to multiple religious buildings distributed across the southwestern USA. Findings of these investigations show that: i)the relocation of the HVAC condensing unit had a dramatic impact on reducing the outdoor wall temperatures and reducing the size of the interior wall moisture area; ii) the porosity of the limestone and large difference between indoor and outdoor temperatures are mainly responsible for the wall deterioration. Finally, outcomes of this article underline the negative impact of a poor intergration of active systems in historic structures, and highlights the necessity for more investigation in this topic.